Trusted Communication in the Internet of Things: Applications of Blockchain and Quantum Technology - Harlita Nindhasari; Harliantara Harliantara; Didik Sugeng W.; Nurannafi FSM (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The rapid expansion and inherent resource limitations of Internet of Things (IoT) devices necessitate robust, future-proof security solutions, particularly against sophisticated data integrity threats and the imminent risk of quantum computing attacks. This paper provides a systematic literature review (SLR) of the architectural integration of blockchain with quantum technologies (quantum key distribution (QKD) and post-quantum cryptography (PQC)) for a two-stage trust model in IoT communication. This review summarizes existing methods and answers three key research questions. The results show that permissioned blockchains are primarily used for trust management to ensure the non-repudiation and immutability of data. Notably, there is a clear dividing line in the application of quantum solutions: QKD is particularly suitable for securing high-capacity backbone communications (server gateways), whereas PQC (especially lattice-based algorithms such as Kyber and Dilithium) is the mainstream resource-efficient solution for IoT terminals. However, this integration also has significant drawbacks, such as high latency due to blockchain consensus mechanisms and increased memory and CPU requirements from PQC implementations. The main challenge is the lack of standardized protocols for integrating QKD key management with smart contract functionality. This review provides a comprehensive analysis of current architectures, assesses their performance trade-offs, and outlines a clear research agenda aimed at developing standardized hybrid protocols for future trusted IoT systems and optimizing resource-efficient, quantum-resistant consensus mechanisms.